Freight data collection using GPS and web-based surveys: Insights from US truck drivers' survey and perspectives for urban freight. Issue 1 (March 2016) - Ben-Akiva, Moshe E.; Toledo, Tomer; Santos, Jorge; Cox, Nathanael; Zhao, Fang; Lee, Yin Jin; Marzano, Vittorio
Highlights: This paper reports on tools, methods and experimental designs developed to study the routing behavior and movement of trucks. These capabilities are demonstrated with a case study on the route choices of North American intercity truck drivers. An extension to the urban freight context, currently ongoing in Singapore, is briefly discussed. The paper demonstrates how advanced sensing and communication technologies can collect previously unattainable freight data. The data reveal in great detail freight travel patterns, enabling next-generation effective and innovative freight models. Abstract: This paper reports on tools, methods and experimental designs that have been developed to study the routing behavior and movement of trucks. The application of these capabilities is demonstrated with a case study on the route choices of North American intercity truck drivers', with a focus on the choice between tolled and free roads. An extension to the urban freight context, currently ongoing in Singapore, is briefly discussed, highlighting the challenges and main differences compared to the intercity case.